TINJAUAN YURIDIS PERTIMBANGAN MAJELIS HAKIM DALAM MENETAPKAN DISPENSASI PERKAWINAN DI BAWAH UMUR (Studi Penetapan Nomor 1837/Pdt.P/2021/PA. Kab. Mlg) - Silvi Chumairotun Nadiyah; Ahmad Subekti; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Underage marriage is a legal act carried out by man and/or women who are not yet 19 years old in a marriage bond. Where to be able to carry out the marriage, you must first obtain a permit in the form of a marriage dispensation from the Religious Court. This study uses a qualitative approach and normative juridical research. while the data collection techniques used are observation, interviews, and documentation. This study describes underage marriage according to Islamic law, the considerations of the panel of judges and underage marriage in the perspective of Law Number 16 of 2019 and KHI. This study reveals that Islamic law does not specifically regulate the age limit for marriage, it can be seen in the absence of arguments that regulate it. Then the phenomenon of underage marriage that occurs in the community, the panel of judges as the holder of authority for the case does not easily grant the application for a marriage dispensation, for that the judge will take into account all aspects. So that the provision of marriage dispensation is in accordance with the provisions of Article 7 paragraphs (1) and (2) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Resistance and Article 15 paragraph (2) of Presidential Instruction Number 1 of 1974. 1991 Concerning the Compilation of Islamic Law. Keywords: Juridical Review, Panel of Judges, Marriage Dispensation, Underage Marriage